Multiplicative and additive methods for the decomposition of the migration rates to/from Tokyo ma., 1985-90 - Ayse Gedik (European Regional Science Association (ERSA), 1998)
My reserch will be about building and empirically testing the model exlaining the net migration to/from the Tokyo Metropolitan Area during 1985-90. This will be interms of interplay of three factors. Firstly, the effects of the "national economic vitality" will be considered. Various studies indicate that not only the national mobility rates, but also the mobility rates to/from the largest metropolitan areas are very sensitive to the changes in the national economy. Secondly, I would like to test the effects of the inter-prefectural disparities between Tokyo M.A. and other prefectures in terms of (mainly): per capita incomes, the differences in the economic structure, supply of higher education. Thirdly, I would like to test the effects of "demographic" factors which will be briefly the age structure of the population and the age-specific mobility rates, and thus the consequent supply of the potential in- and out-migrants to/from the Tokyo M.A. The study of experience of Japan, with very high level of urbanization, with give very valuable and necessary insights to countries with lower level of urbanization in order for them to plan and predict the growth of their largest cities in future.
Keywords: 330